A solution to the problem of too many instruments in dynamic panel data GMM - Jens Mehrhoff (Deutsche Bundesbank, 2009)
The well-known problem of too many instruments in dynamic panel data GMM is dealt with in detail in Roodman (2009, Oxford Bull. Econ. Statist.). The present paper goes one step further by providing a solution to this problem: factorisation of the standard instrument set is shown to be a valid transformation for ensuring consistency of GMM. Monte Carlo simulations show that this new estimation technique outperforms other possible transformations by having a lower bias and RMSE as well as greater robustness of overidentifying restrictions. The researcher's choice of a particular transformation can be replaced by a data-driven statistical decision.
Keywords: C13; C15; C23; C81; 330; Dynamic panel data; generalised method of moments; instrument proliferation; factor analysis; Panel; Momentenmethode; Faktorenanalyse; Theorie